Aluminum alloy, preparation method and application thereof

CN122979710APending Publication Date: 2026-10-27BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611191347.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明提供一种铝合金及其制备方法与应用,用以解决现有3003 铝合金强度不足、6063 铝合金钎焊性能差与耐蚀性不佳,单一铝合金材料无法同时兼顾优良高强力学性能、耐蚀钎焊性能与耐腐蚀性能的缺陷,实现铝合金材料兼具高强度、高耐腐蚀性能和优良钎焊性能的效果

Benefits of technology

本发明第一方面提供的铝合金,突破了传统铝合金依赖Mg2Si析出强化的技术瓶颈,创新性地利用Mn、Cu、V、Cr四种元素的协同作用,构建起新的固溶强化和弥散强化的复合强化体系。该合金以Al-Mn体系为基础,通过Cu、V、Cr的协同添加,在单一基体中同时实现了高强度、高耐蚀性与优良钎焊性:其强度较传统合金获得大幅提升,且强化机制不依赖Mg元素;力学强度上达到或超越6063铝合金水平,同时在耐腐蚀性和钎焊性能上保持与3003铝合金相当或更优的表现,展现出优异的综合性能优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979710A_ABST
    Figure CN122979710A_ABST
Patent Text Reader

Abstract

The application provides an aluminum alloy and a preparation method and application thereof, and relates to the technical field of aluminum alloys.The aluminum alloy comprises the following components in percentage by weight: manganese 1.0-1.8%; copper 0.2-0.8%; vanadium 0.05-0.2%; chromium 0.05-0.2%; and the rest is aluminum and inevitable impurities.The aluminum alloy provided by the application utilizes the synergistic effect of Mn, Cu, V and Cr to solve the defects of the existing 3003 aluminum alloy, such as insufficient strength, the poor brazing performance and poor corrosion resistance of the 6063 aluminum alloy, and the single aluminum alloy material cannot simultaneously have excellent high-strength mechanical properties, brazing performance and corrosion resistance, so that the aluminum alloy material has the effects of high strength, high corrosion resistance and excellent brazing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy technology, and in particular to an aluminum alloy, its preparation method, and its application. Background Technology

[0002] Existing power unit heat exchangers, liquid cooling plates, and radiators are equipped with flow channels for the circulation of a cooling medium (usually a ethylene glycol aqueous solution with a specific ratio) at a specific flow rate and temperature. Heat exchange is used to dissipate heat (heat) from components requiring specific heat dissipation (heating). In the field of heat exchange and pressure-bearing components such as heat exchangers, liquid cooling plates, and radiators, 3003 aluminum-manganese alloys and 6063 aluminum-magnesium-silicon alloys are currently the two most widely used base materials. However, both have significant performance shortcomings, making it difficult to meet comprehensive service requirements. 3003 aluminum alloy, relying on the solid solution strengthening effect of manganese, possesses excellent resistance to pitting corrosion and intergranular corrosion, and exhibits good high-temperature brazing stability and brazing filler metal spreadability, making it suitable for brazing assembly processes of heat exchange components. However, this alloy cannot be heat-treated for strengthening; its annealed O-state tensile strength is only about 110 MPa, resulting in low overall mechanical properties that cannot meet the pressure-bearing requirements under high-pressure and high-load conditions.

[0003] 6063 aluminum alloy can achieve Mg2Si precipitation strengthening through heat treatment, with a tensile strength exceeding 165 MPa in the T5 state, demonstrating significant mechanical property advantages and making it suitable for high-pressure components. However, the magnesium in the alloy is prone to volatilization during high-temperature brazing, reacting with fluoride flux to severely poison the brazing atmosphere, leading to a sharp deterioration in brazing spreadability and a significant reduction in welding reliability. Simultaneously, the Mg2Si phase, dispersed in the matrix, has a lower potential than the aluminum matrix, making it prone to inducing pitting corrosion as an anode, resulting in significantly weaker corrosion resistance compared to 3003 aluminum alloy. Currently, the industry lacks a single aluminum alloy material that can combine the corrosion resistance and brazing performance of 3003 with the high-strength mechanical properties of 6063, indicating a clear bottleneck in material performance. Summary of the Invention

[0004] This invention provides an aluminum alloy, its preparation method, and its application, to address the shortcomings of existing 3003 aluminum alloy (insufficient strength), 6063 aluminum alloy (poor brazing performance and corrosion resistance), and the inability of a single aluminum alloy material to simultaneously achieve excellent high-strength mechanical properties, corrosion-resistant brazing performance, and corrosion resistance. This invention achieves the effect of aluminum alloy materials possessing high strength, high corrosion resistance, and excellent brazing performance.

[0005] In a first aspect, the present invention provides an aluminum alloy comprising, by weight percentage: Manganese: 1.0% ~ 1.8%; Copper: 0.2% ~ 0.8%; Vanadium: 0.05% ~ 0.2%; Chromium: 0.05% ~ 0.2%; The remainder consists of aluminum and unavoidable impurities.

[0006] In a second aspect, the present invention provides a method for preparing an aluminum alloy as described in the first aspect, comprising the following steps: melting the alloy according to the proportion, casting it into an ingot, homogenizing it at 550~620°C, processing it into shape, and then annealing it at 300~400°C to obtain the aluminum alloy.

[0007] In a third aspect, the present invention provides an aluminum alloy article comprising an aluminum alloy as described in the first aspect, or an aluminum alloy prepared by the preparation method described in the second aspect.

[0008] In a fourth aspect, the present invention provides a power device comprising an aluminum alloy as described in the first aspect, an aluminum alloy prepared by the method described in the second aspect, or an aluminum alloy article as described in the third aspect.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: The aluminum alloy provided by the first aspect of this invention breaks through the technical bottleneck of traditional aluminum alloys relying on Mg2Si precipitation strengthening. It innovatively utilizes the synergistic effect of four elements—Mn, Cu, V, and Cr—to construct a new composite strengthening system of solid solution strengthening and dispersion strengthening. Based on the Al-Mn system, this alloy achieves high strength, high corrosion resistance, and excellent brazing properties simultaneously in a single matrix through the synergistic addition of Cu, V, and Cr. Its strength is significantly improved compared to traditional alloys, and the strengthening mechanism does not depend on Mg. Its mechanical strength reaches or exceeds that of 6063 aluminum alloy, while maintaining or surpassing the performance of 3003 aluminum alloy in corrosion resistance and brazing properties, demonstrating excellent comprehensive performance advantages. Attached Figure Description

[0010] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0011] Figure 1 This is a schematic diagram of the corrosion depth ratio in Test Example 1. Detailed Implementation

[0012] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0013] Unless otherwise specified in the embodiments of this invention, the techniques or conditions described in the literature in this field, or the product instructions, shall apply. Devices, instruments, reagents, etc., whose manufacturers are not specified, are all conventional products that can be purchased through legitimate channels. All raw materials used in this invention are readily available in the domestic market.

[0014] In this invention, the technical features described in an open-ended manner include both closed-ended technical solutions composed of the listed features and open-ended technical solutions that include the listed features.

[0015] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.

[0016] In a first aspect, the present invention provides an aluminum alloy comprising, by weight percentage: Manganese (Mn): 1.0% ~ 1.8%; Copper (Cu): 0.2% ~ 0.8%; Vanadium (V): 0.05% ~ 0.2%; Chromium (Cr): 0.05% ~ 0.2%; The remainder consists of aluminum (Al) and unavoidable impurities.

[0017] The aluminum alloy provided by the first aspect of this invention uses Mn as the core corrosion-resistant element. Controlling its content within the range of 1.0% to 1.8% achieves excellent corrosion resistance and brazing performance comparable to alloy 3003. When the Mn content is below 1.0%, the aluminum alloy's strength and corrosion resistance are insufficient; when the content exceeds 1.8%, the aluminum alloy easily forms coarse Al6Mn phases, impairing processing plasticity and toughness. Cu, as the core solid solution strengthening element, is controlled within the range of 0.2% to 0.8%. This significantly improves the strength of the aluminum alloy while avoiding significant deterioration in corrosion resistance (especially intergranular corrosion tendency) due to excessive copper. The synergistic addition of V and Cr elements, with their contents controlled within the ranges of 0.05% to 0.2% and 0.05% to 0.2% respectively, forms a more stable and dispersed strengthening phase than a single element, producing an unexpected synergistic strengthening effect without compromising corrosion resistance.

[0018] In the aluminum alloy provided by this invention: Manganese (Mn): 1.0% ~ 1.8%, for example, it can be selected as 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8% or any range formed by any two of the above values; Copper (Cu): 0.2% ~ 0.8%, for example, it can be selected as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or any range formed by any two of the above values; Vanadium (V): 0.05% ~ 0.2%, for example, it can be selected as 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20% or any range formed by any two of the above values; Chromium (Cr): 0.05% ~ 0.2%, for example, it can be selected as 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20% or any range formed by two of the above values.

[0019] In some embodiments, the magnesium content in the aluminum alloy is ≤ 0.05%, such as 0.05%, 0.04%, 0.03%, 0.02%, 0.01%, 0, or any two of the above values, preferably ≤ 0.03%.

[0020] In this solution, the magnesium content in the aluminum alloy is controlled within the range of ≤ 0.05%, especially within the range of ≤ 0.03%, which eliminates the problem of "brazing poisoning" caused by Mg volatilization during brazing from the root, ensuring that the alloy has the same excellent brazing performance as 3003.

[0021] In some embodiments, the weight percentage of iron in the aluminum alloy is a, where 0 < a ≤ 0.3%, such as 0.3%, 0.28%, 0.25%, 0.23%, 0.20%, 0.18%, 0.15%, 0.12%, 0.10%, 0.08%, 0.05%, 0.02%, 0, or any range formed by two of the above values, preferably 0 < a ≤ 0.2%.

[0022] In this scheme, controlling 0 < a ≤ 0.3%, especially within the range of 0 < a ≤ 0.2%, effectively avoids the formation of coarse needle-like iron-rich phases and significantly reduces the corrosion susceptibility of the alloy. Simultaneously, trace amounts of iron can synergistically interact with Mn, V, and Cr to form a more stable nanoscale multi-element dispersed phase, further enhancing the dispersion strengthening effect while ensuring the alloy's high plasticity and processability.

[0023] In some embodiments, the weight percentage of silicon in the aluminum alloy is b, where 0 < b ≤ 0.3%, such as 0.3%, 0.28%, 0.25%, 0.23%, 0.20%, 0.18%, 0.15%, 0.12%, 0.10%, 0.08%, 0.05%, 0.02%, or any range formed by two of the above values, preferably 0 < b ≤ 0.2%.

[0024] In this scheme, controlling 0 < b ≤ 0.3%, especially within the range of 0 < b ≤ 0.2%, effectively suppresses the formation of the Mg2Si phase, ensuring that the aluminum alloy possesses both excellent brazing properties and high corrosion resistance. Simultaneously, controlling Si and impurity Fe synergistically at low levels effectively inhibits the formation of coarse, needle-like β-AlFeSi harmful phases. Furthermore, under the specific V, Cr composite addition system of this invention, strictly controlling trace amounts of Si within a defined range promotes the formation of finer, more dispersed multi-element silicon-containing reinforcing phases, producing an auxiliary strengthening effect.

[0025] In some of these implementations, Manganese: 1.2% ~ 1.7%; And / or, copper: 0.3% ~ 0.7%; And / or, vanadium: 0.10% ~ 0.18%; And / or, chromium: 0.08% ~ 0.16%.

[0026] In this scheme, the manganese, copper, vanadium and chromium in the aluminum alloy are controlled within the ranges of 1.2% ~ 1.7%, 0.3% ~ 0.7%, 0.10% ~ 0.18% and 0.08% ~ 0.16%, respectively, which further achieves a synergistic improvement effect of high strength, high corrosion resistance and excellent brazing performance of aluminum alloy materials.

[0027] In some embodiments, vanadium and chromium are dispersed in the aluminum alloy in the form of vanadium and chromium nanoparticles.

[0028] In this scheme, vanadium and chromium are dispersed in the aluminum alloy in the form of vanadium and chromium nanoparticles, which can play a dispersion strengthening role.

[0029] In some embodiments, the tensile strength of the aluminum alloy is ≥195MPa, such as 195MPa, 200MPa, 205MPa, 210MPa, 215MPa, 220MPa, 225MPa, 230MPa, 235MPa, 240MPa, 245MPa or any range formed by any two of the above values; the yield strength is ≥153MPa, such as 153MPa, 155MPa, 160MPa, 165MPa, 170MPa, 175MPa, 180MPa, 185MPa, 190MPa, 195MPa, 198MPa or any range formed by any two of the above values.

[0030] In some embodiments, the corrosion depth of the aluminum alloy is less than 10%.

[0031] In a second aspect, the present invention provides a method for preparing an aluminum alloy as described in the first aspect, comprising the following steps: melting the alloy according to the proportion, casting it into an ingot, homogenizing it at 550~620°C, processing it into shape, and then annealing it at 300~400°C to obtain the aluminum alloy.

[0032] By employing a synergistic composite addition of V and Cr elements, with V and Cr contents controlled within the ranges of 0.05%~0.2% and 0.05%~0.2% respectively, fine, dispersed V / Cr nanoparticles can be formed during homogenization treatment at 550~620℃. These particles not only effectively pin grain boundaries, inhibit recrystallization and grain growth, thus playing a dispersion strengthening role, but also, through the synergistic effect of V and Cr, form a more stable and dispersed strengthening phase than either element alone, producing an unexpected synergistic strengthening effect without compromising corrosion resistance.

[0033] The homogenization treatment is controlled within the range of 550~620℃, which is higher than the rapid diffusion temperature of Mn. This effectively eliminates dendritic segregation in the as-cast state, making the distribution of elements such as Mn and Cu more uniform. At the same time, it avoids the occurrence of liquid phase due to excessively high temperature, which can lead to overheating. The annealing temperature is controlled within the range of 300~400℃, which allows the cold-deformed structure to recrystallize, eliminates work hardening, and allows the dispersed phases containing V and Cr to precipitate stably at this stage.

[0034] In the method for preparing aluminum alloy provided by this invention: The homogenization process is carried out at a temperature of 550~620℃. For example, it can be selected as 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃ or any two of the above values. The annealing temperature is 300~400℃. For example, it can be selected as 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃ or any range formed by any two of the above values.

[0035] In some embodiments, the homogenization process takes 6 to 24 hours, such as 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, or any range formed by any two of the above values, and / or the annealing process takes 1 to 4 hours, such as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, or any range formed by any two of the above values.

[0036] In some embodiments, the forming process includes hot working and cold working, wherein the hot working includes hot rolling or hot extrusion, and the cold working includes cold rolling or cold drawing.

[0037] A third aspect of the present invention provides an aluminum alloy article comprising the aluminum alloy described in the first aspect.

[0038] In some embodiments, the aluminum alloy product includes at least one of a heat exchanger, a liquid cooling plate, a radiator, and an intercooler.

[0039] A fourth aspect of the present invention provides an application of aluminum alloy articles as described in the third aspect in vehicles.

[0040] The present invention will be further described below with reference to embodiments. These embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.

[0041] Example 1 1. This embodiment provides an aluminum alloy, which, by weight percentage, comprises: Manganese: 1.5%; Copper: 0.5%; Vanadium: 0.15%; Chromium: 0.12%; The remainder consists of aluminum and unavoidable impurities; The aluminum alloy contains 0.03% magnesium. The iron content in the aluminum alloy is 0.2%; The aluminum alloy contains 0.2% silicon. Vanadium and chromium are dispersed in the aluminum alloy in the form of vanadium and chromium nanoparticles.

[0042] 2. This embodiment also provides a method for preparing the above-mentioned aluminum alloy, including the following steps: a) Smelting and casting: According to the above composition ratio, the alloy melt is smelted and prepared at 720~750℃, and after refining and purification, it is cast into alloy ingots. b) Homogenization treatment: The alloy ingot is held at 550℃ for 12 hours for homogenization treatment; c) Hot and cold working: The homogenized alloy ingot is hot rolled to a 4mm thick plate, and then cold rolled to a final thickness of 1.5mm; d) Heat treatment: The cold-rolled sheet is annealed at 360℃ for 2 hours to obtain O-state aluminum alloy.

[0043] Example 2 1. This embodiment provides an aluminum alloy, which, by weight percentage, comprises: Manganese: 1.8%; Copper: 0.8%; Vanadium: 0.05%; Chromium: 0.05%; The remainder consists of aluminum and unavoidable impurities; The aluminum alloy contains 0.03% magnesium. The iron content in the aluminum alloy is 0.2%; The aluminum alloy contains 0.2% silicon. Vanadium and chromium are dispersed in the aluminum alloy in the form of vanadium and chromium nanoparticles.

[0044] 2. The difference between the preparation method of the aluminum alloy provided in this embodiment and that in embodiment 1 is that the aluminum alloy composition ratio provided in this embodiment is followed.

[0045] Example 3 1. This embodiment provides an aluminum alloy, which, by weight percentage, comprises: Manganese: 1%; Copper: 0.2%; Vanadium: 0.2%; Chromium: 0.2%; The remainder consists of aluminum and unavoidable impurities; The aluminum alloy contains 0.03% magnesium. The iron content in the aluminum alloy is 0.2%; The aluminum alloy contains 0.2% silicon. Vanadium and chromium are dispersed in the aluminum alloy in the form of vanadium and chromium nanoparticles.

[0046] 2. The difference between the preparation method of the aluminum alloy provided in this embodiment and that in embodiment 1 is that the aluminum alloy composition ratio provided in this embodiment is followed.

[0047] Example 4 1. This embodiment provides an aluminum alloy, which differs from Embodiment 1 in that: magnesium: 0.06%.

[0048] 2. The difference between the preparation method of the aluminum alloy provided in this embodiment and that in embodiment 1 is that the aluminum alloy composition ratio provided in this embodiment is followed.

[0049] Comparative Example 1 Commercially available 3003-O state aluminum alloy.

[0050] Comparative Example 2 Commercially available 6063-T5 aluminum alloy.

[0051] Comparative Example 3 1. This comparative example provides an aluminum alloy, which differs from Example 1 in that: manganese: 2.6%.

[0052] 2. The difference between the preparation method of the aluminum alloy provided in this comparative example and that in Example 1 is that the aluminum alloy composition ratio provided in this comparative example is followed.

[0053] Comparative Example 4 1. This comparative example provides an aluminum alloy, which differs from Example 1 in that: copper: 1.5%.

[0054] 2. The difference between the preparation method of the aluminum alloy provided in this comparative example and that in Example 1 is that the aluminum alloy composition ratio provided in this comparative example is followed.

[0055] Comparative Example 5 1. This comparative example provides an aluminum alloy that differs from Example 1 in that it contains 0.27% vanadium.

[0056] 2. The difference between the preparation method of the aluminum alloy provided in this comparative example and that in Example 1 is that the aluminum alloy composition ratio provided in this comparative example is followed.

[0057] Comparative Example 6 1. This comparative example provides an aluminum alloy, which differs from Example 1 in that: chromium: 0.25%.

[0058] 2. The difference between the preparation method of the aluminum alloy provided in this comparative example and that in Example 1 is that the aluminum alloy composition ratio provided in this comparative example is followed.

[0059] Test Example 1 (1) Tensile test: The mechanical properties at room temperature were tested according to GB / T 228.1-2021 standard.

[0060] (2) Brazing performance test: The sample with a size of 50mm×50mm was brazed in a furnace at 600℃ for 3 minutes using potassium fluoroaluminate flux. The spread of the brazing filler metal (4045 alloy) on the surface was observed, the spread area was measured, and the brazing performance was evaluated based on the spread area.

[0061] (3) Corrosion resistance test: Corrosion resistance tests were conducted according to the national standard GB29743.2-2025 (Static Corrosion Test Method for Tram Coolant), with the aluminum alloy 3003 sample piece replaced by the aluminum alloy of the same specification prepared in the above-mentioned examples and comparative examples. Test Results ① No leaks are allowed after the test is completed; ② After the test, the corrosion condition of the inner wall surface (coolant contact surface) is confirmed by electron microscopy, and no pitting corrosion is required. ③ If pitting corrosion occurs, perform metallographic measurement of the corrosion depth of the pitting corrosion. It is required that the corrosion depth of all measured pitting corrosion points shall not exceed 10% of the thickness of the raw material.

[0062] The test results of the aluminum alloys provided in the above embodiments and comparative examples are shown in Table 1 below. In Table 1: Brazing performance: Based on the area of ​​the sample surface on the brazing filler side, a brazing filler area ratio >85% is rated as excellent; a brazing filler area ratio of 50%~85% is rated as poor; and a brazing filler area ratio <50% is rated as very poor. Corrosion resistance: ① Quality change: Quality change ≤ 10mg, rated as qualified; quality change > 10mg, rated as unqualified; ② Corrosion status: No pitting is rated as excellent; 1-5 pitting points are rated as good; some pitting points are present; more than 5 pitting points are rated as poor, indicating a large number of pitting points. ③ Corrosion Depth Ratio: The corrosion depth ratio is the proportion of the maximum corrosion depth among pitting corrosion points. Corrosion depth ratio = corrosion depth / original wall thickness. See the schematic diagram below. Figure 1 .

[0063] Table 1

[0064] As shown in Table 1: The aluminum alloys provided in Examples 1-3 of this invention have a tensile strength ≥195MPa, a yield strength ≥153MPa, an elongation ≥12.5%, and brazing performance comparable to 3003 aluminum alloy. In addition, in the corrosion resistance test, after resisting coolant corrosion, the corrosion depth ratio is <10%.

[0065] However, Comparative Examples 3 to 6 could not produce aluminum alloy materials that simultaneously possess high strength, excellent corrosion resistance, and good brazing performance because the content of their key metal elements did not fall within the proportion range defined by this invention.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aluminum alloy, characterized in that, The aluminum alloy comprises, by weight percentage: Manganese: 1.0% ~ 1.8%; Copper: 0.2% ~ 0.8%; Vanadium: 0.05% ~ 0.2%; Chromium: 0.05% ~ 0.2%; The remainder consists of aluminum and unavoidable impurities.

2. The aluminum alloy according to claim 1, characterized in that, The aluminum alloy contains ≤ 0.05% magnesium, preferably ≤ 0.03%.

3. The aluminum alloy according to claim 1 or 2, characterized in that, The weight percentage of iron in the aluminum alloy is a, where 0 < a ≤ 0.3%, preferably 0 < a ≤ 0.2%.

4. The aluminum alloy according to any one of claims 1 to 3, characterized in that, The weight percentage of silicon in the aluminum alloy is b, where 0 < b ≤ 0.3%, preferably 0 < b ≤ 0.2%.

5. The aluminum alloy according to any one of claims 1 to 4, characterized in that, Manganese: 1.2% ~ 1.7%; And / or, copper: 0.3% ~ 0.7%; And / or, vanadium: 0.10% ~ 0.18%; And / or, chromium: 0.08% ~ 0.16%.

6. The aluminum alloy according to any one of claims 1 to 4, characterized in that, The aluminum alloy has a tensile strength ≥195MPa and a yield strength ≥153MPa.

7. The aluminum alloy according to any one of claims 1 to 4, characterized in that, The corrosion depth ratio of the aluminum alloy is <10%.

8. A method for preparing an aluminum alloy as described in any one of claims 1 to 7, characterized in that, Includes the following steps: The alloy is smelted according to the proportion, cast into ingots, homogenized at 550~620℃, shaped, and then annealed at 300~400℃ to obtain the aluminum alloy.

9. The method for preparing the aluminum alloy according to claim 8, characterized in that, The homogenization process takes 6 to 24 hours, and / or the annealing process takes 1 to 4 hours.

10. An aluminum alloy product, characterized in that, The aluminum alloy article includes the aluminum alloy as described in any one of claims 1 to 7, or the aluminum alloy prepared by the preparation method as described in claim 8 or 9.

11. The aluminum alloy product according to claim 10, characterized in that, The aluminum alloy product includes a heat exchanger; Preferably, the heat exchanger includes at least one of a liquid cooling plate, a radiator, and an intercooler.

12. A power unit, characterized in that, The power unit comprises the aluminum alloy as described in any one of claims 1 to 7, or the aluminum alloy prepared by the method described in claim 8 or 9, or the aluminum alloy article as described in claim 10. Preferably, the power unit includes at least one of a vehicle, a robot, and an energy storage device.